Design of Simple Acoustic Materials for High School Hall Using Software CATT - Maria Christina Prasetya (Universitas Atma Jaya Yogyakarta, 2022)
Good acoustic quality is essential to consider in designing a multipurpose room. Unfortunately, school halls usually have poor room acoustics. Lack of funds and lack of knowledge about acoustics cause the acoustic quality of the room to be very poor. The purpose of this research is to design a simple acoustic material application concept for a high school hall based on the Ministry of Education and Culture manual to meet the requirements for speech, music, and sports functions. Simple acoustic materials exist in everyday life, such as corrugated cardboard, cork, multiplex boards, newspapers, egg racks, and cloth. The research applied a simulation method using CATT v8 software. The parameters used to measure room acoustic quality were RT60, C-80, D-50, STI, EDT, and LF The simulation compared the hall's acoustic performance without and with the simple sound absorbers. The absorbers were applied to 39% of the walls and 55% ceilings. The absorbers reduced T-30 (500Hz) from 3.8 seconds to 1.5 seconds with an omni sound source and 1.3 seconds with speakers. The averaged Speech Transmission Index (STI) was improved from 38% to 60% with the omni sound source and from 43% to 65% with speakers.